Diagnostic challenge in a rare case of neuroendocrine tumor of the pancreas (Indian Journal of Case Reports, 2020)
A pancreatic neuroendocrine tumor is a rare disease with varying behavior, clinical, and microscopic appearances. We present a case of neuroendocrine tumor of the pancreas in a 63-year-old female. Right from the beginning, our case was a diagnostic challenge from the clinical and radiological perspective. Radiological features can often be misleading and microscopic confirmation is all-important. This case report describes the approach to the diagnosis of such a case combining clinical, radiological, and pathological aspects to ensure proper management of the patient.